The Conservation Efforts of Wood Apple, An Identity Plant of Rembang Regency, Based on Ethnobotany Study - Enni Suwarsi Rahayu; Nur Kusuma Dewi; Lina Herlina; Talitha Widiatningrum (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Feronia limonia (L.) Swingle better known as wood apple is an identity plant of Rembang Regency, Central Java Province, Indonesia. However, the population is very limited. In order to identify the conservation efforts, this ethnobotany study was aimed to determine traditional knowledge on the existence, economic value, utility, breeding technique and conservation of wood apple. The survey was conducted on a total of 102 local people from 10 sub-districts which were determined by proportionally stratified random sampling. Data were collected by questionnaires and individual interviews and then were analyzed descriptively. The results showed that all of respondents knew the figure of wood apple, but only 79.50% understood its status as an identity plant. Most of respondents (96%) stated that the fruits have low economic value, 80.39% respondents have utilized ripe fruit as ingredients of beverages and stems as firewood. This utilization was only equal to 29.72% compared to the potential usability based on research results. It was concluded that the traditional knowledge about the existence, economic value, and breeding technique were good and on the contrary, the knowledge about the plant’s usability was bad. The results will form a basic knowledge for in-depth studies to provide a government policy of Rembang Regency in order to develop an efficient strategy of management and conservation of wood apple as plant identity.